ENHANCING BOTH COMPANIES AND CONSUMERS’ INTENTION TO BOTH PRODUCE AND CONSUME GREEN PRODUCT - Wilson, Nicholas (Jurnal Pengabdian dan Kewirausahaan, 2022)
Green business, green marketing or sustainable business activities had emerged as some of the most discussed and most popular concept within the realm of business, in which, due to the continuous destruction of wildlife and environment all around the world, many people, non-governmental organizations, entrepreneurs, companies and government had constantly pushed and urged many businesses to do or conduct their business activities in a proper and sustainable way which won’t have any damaging or negative impact toward the surrounding environment. Meanwhile, at the same time, consumers were also constantly being “pushed” by these same parties to play a more active role in ensuring that the negative impact of these business activities toward the environment won’t escalate by stop consuming, buying or using non-green product which is not sustainable and could bring a dire impact toward the nature and the surrounding environment in the future. Therefore, this community services activities were designed or conducted in order to give some information, suggestions, or understanding to both businesses and consumers, not only in order to ensure that both of these parties will fully understand the main concept of green business, but also in order to ensure that both parties will eventually and actually conduct both of their businesses and consumption activities in a more sustainable way